The influence of protein malnutrition on the production of GM-CSF and M-CSF by macrophages - Dalila Cunha de Oliveira; Araceli Aparecida Hastreiter; Primavera Borelli; Ricardo Ambrósio Fock
ABSTRACT It is well established that protein malnutrition (PM) impairs immune defenses and increases susceptibility to infection. Macrophages are cells that play a central role in innate immunity, constituting one of the first barriers against infections. Macrophages produce several soluble factors, including cytokines and growth factors, important to the immune response. Among those growth factors, granulocyte-macrophage colony-stimulating factor (GM-CSF) and macrophage colony-stimulating factor (M-CSF). GM-CSF and M-CSF are important to monocyte and macrophage development and stimulation of the immune response process. Knowing the importance of GM-CSF and M-CSF, we sought to investigate the influence of PM on macrophage production of these growth factors. Two-month-old male BALB/c mice were subjected to PM with a low-protein diet (2%) and compared to a control diet (12%) mouse group. Nutritional status, hemogram and the number of peritoneal cells were evaluated. Additionally, peritoneal macrophages were cultured and the production of GM-CSF and M-CSF and mRNA expression were evaluated. To determine if PM altered macrophage production of GM-CSF and M-CSF, they were stimulated with TNF-α. The PM animals had anemia, leukopenia and a reduced number of peritoneal cells. The production of M-CSF was not different between groups; however, cells from PM animals, stimulated with or without TNF-α, presented reduced capability to produce GM-CSF. These data imply that PM interferes with the production of GM-CSF, and consequently would affect the production and maturation of hematopoietic cells and the immune response.